2004
DOI: 10.1002/ana.20105
|View full text |Cite
|
Sign up to set email alerts
|

Role of cerebral lateralization in control of immune processes in humans

Abstract: Cerebral lateralization may be important in neural control of immune function. Animal studies have demonstrated differential effects of left and right brain lesions on immune function, but human studies are inconclusive. Here, we show that resections in the language dominant hemisphere of patients with epilepsy reduce lymphocytes, total T cells, and helper T cells. In contrast, resections in the language nondominant hemisphere increased the same cellular elements. T-cell responses to mitogens and microbial ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…Bauer et al (2009) showed that patients with well-characterized TLE led to immediate and long lasting posictal increase in systemic IL-6 levels; however this rise of IL-6 was lacking in patients with hippocampal sclerosis. The authors in accord with Meador et al,(2004) suggest the cerebral lateralization of immune functions. On the other hand, there was expression of proinflammatory molecules in neurons and glia in brain tissue obtained from patients surgically treated for drug-resistant epilepsies (Crespel et al, 2002;Maldonado et al, 2003).…”
Section: Temporal Lobe Epilepsy (Tle)supporting
confidence: 72%
“…Bauer et al (2009) showed that patients with well-characterized TLE led to immediate and long lasting posictal increase in systemic IL-6 levels; however this rise of IL-6 was lacking in patients with hippocampal sclerosis. The authors in accord with Meador et al,(2004) suggest the cerebral lateralization of immune functions. On the other hand, there was expression of proinflammatory molecules in neurons and glia in brain tissue obtained from patients surgically treated for drug-resistant epilepsies (Crespel et al, 2002;Maldonado et al, 2003).…”
Section: Temporal Lobe Epilepsy (Tle)supporting
confidence: 72%
“…Future studies also need to investigate why the right cerebellum, and not the left or both cerebella, was hyperactive in the malignancy cases, given known lateralization and immunity findings (20). Finally, the prognostic role of these findings should also be investigated in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, women were recently reported to harbor more single cysticercotic calcified lesions in their right cerebral hemisphere than in the left. Presumably, lateralization of calcified cysticerci reflects the differential immunological abilities between the cerebral hemispheres (Meador et al, 2004). Although no sexual differences in these cerebral abilities have been notified, cysticercus lateralization is not found in male neurocysticercotic patients.…”
Section: Experimental T Solium Taeniosis/cysticercosismentioning
confidence: 96%